Whey as a renewable source for lipid production by Rhodococcus strains: Physiology and genomics of lactose and galactose utilization - Herrero, Ornella Marisa (2016)
We investigated biomass and lipid production from whey by different Rhodococcus strains. The studied microorganisms exhibited different capability for growing and producing lipids from whey permeate. Strains belonging to R. opacus exhibited high yields of biomass (6.1–6.3 g/L) and lipid content (45–48% of CDW), whereas R. jostii, R. erythropolis, R. fascians, and R. equi strains produced low biomass (1.8–2.9 g/L) and lipids (lesser than 5% of CDW) from whey. Lactose and galactose, which are main constituents of whey, supported growth of R. opacus strains, but not of the other investigated species. A genome‐wide bioinformatic analyses demonstrated that some genes coding for transport systems (LacEFGK) and the β‐galactosidase (LacB) enzyme for lactose cleavage are lacking in such species, which may explain their inability to utilize lactose, galactose, and whey for an efficient biomass and lipid production. R. opacus possesses a complete genetic endowment for degrading lactose, galactose, and whey as well as for lipid biosynthesis from such substrates. Thus, R. opacus is a robust candidate for single‐cell oil production from whey. The cultivation of R. opacus cells on crude whey resulted in an increase of lipid production from 3.0 to 6.4 g/L, in comparison to whey permeate. Practical application: This study demonstrates that the bioconversion of whey to oils by Rhodococcus strains is feasible. However, we found some genetic and physiological differences for whey, lactose and galactose catabolism and assimilation among rhodococcal species. Our results demonstrate that among five different rhodococcal species, Rhodococcus opacus has the more robust genetic endowment for supporting high yields of biomass and lipid production from whey. The use of whey for single cell oil production by rhodococci may serve as platform for developing environmentally friendly biotechnological processes.